Potential for arsenic contamination of rice in Bangladesh: spatial analysis and mapping of high risk areas. (24th April 2006) - Ross, Zev; Duxbury, John M.; DeGloria, Stephen D.; Paul, Debi Narayan Rudra
Knowledge of the location and severity of arsenic contamination in Bangladesh is required to develop land and resource management strategies to reduce human exposure to arsenic and arsenic contamination of food and water supplies. Potential high risk areas for arsenic contamination of rice were identified using spatial analysis and modelling. Existing country-wide data on groundwater arsenic contamination, winter (boro) rice production and irrigation methods were used to identify areas where high production of groundwater irrigated boro rice corresponds to areas with high arsenic contamination of groundwater. Results show that 76% of irrigated boro rice is grown in upazila where mean groundwater arsenic concentrations are below 50 µg L -1, the Bangladesh health standard. Seven percent, however, is grown in areas with mean concentrations greater than 100 µg L -1, primarily in south-central and western-central Bangladesh. Mitigation strategies are suggested for the areas considered to be at risk for arsenic contamination of boro rice.